2023
DOI: 10.1007/s13760-023-02336-5
|View full text |Cite
|
Sign up to set email alerts
|

Miller Fischer syndrome after COVID-19 infection and vaccine: a systematic review

Abstract: Background COVID-19 (CoranaVirus disease 2019) is an ongoing infectious disease caused by the RNA SARS-CoV-2 virus (Severe Acute Respiratory Syndrome CoronaVirus-2). The virus mainly causes respiratory symptoms, but neurological symptoms have also been reported to be part of the clinical manifestations of the disease. The aim of this study was to systematically review Miller fisher syndrome (MFS) published cases, in the context of COVID-19 infection or vaccination. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Searching for previously reported relevant scientific articles and literature found no cases of MFS associated with SARS cov-2 in the Republic of Kazakhstan. However, there was only one case of MFS has been described in the Russian Federation [8,9]. Researchers who conducted genetic analyses of COVID-19 recovered patients discovered that Asians and individuals of African descent experienced more severe outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for previously reported relevant scientific articles and literature found no cases of MFS associated with SARS cov-2 in the Republic of Kazakhstan. However, there was only one case of MFS has been described in the Russian Federation [8,9]. Researchers who conducted genetic analyses of COVID-19 recovered patients discovered that Asians and individuals of African descent experienced more severe outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although a rare occurrence, multiple cases of MFS following COVID-19 vaccination have been described across several countries ( 48 50 ). Unlike GBS associated with vaccination, it does not appear to be related to the viral vector vaccination ( 51 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Reyes-Bueno et al detailed the post-COVID-19 Miller Fisher syndrome (MFS) reported in some patients which included complaints of blurred vision and extra-ocular muscle palsy [ 55 ]. Neophytou et al published a systematic review of this syndrome in COVID-19 patients with a conclusion that the condition occurred more frequently after infection as compared to after vaccination [ 56 ]. The prognosis of MFS is spontaneous and very good even without administering intravenous immunoglobulin [ 56 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%
“…Neophytou et al published a systematic review of this syndrome in COVID-19 patients with a conclusion that the condition occurred more frequently after infection as compared to after vaccination [ 56 ]. The prognosis of MFS is spontaneous and very good even without administering intravenous immunoglobulin [ 56 ].…”
Section: Ocular Manifestations Of Covid-19mentioning
confidence: 99%